The Characterisrics And Failure Mechanisms Of Creep And Creep-Thermal Cycling Of Superheater Tube - Suprapto, Agus (2000)

(untitled)
Most of superheated tubes of power plants using oil as fuel have premature failures usually caused by mechanical and corrosion failure. The application of superheated boiler tube includes a sequence of events such as fluctuating stress levels at constant temperature, fluctuating temperature levels at constant stress, and periods during which both stress and temperature are simultaneously fluctuating. This is supported by evidence indicating that the thermal cycling and creep processes interact to produce a synergistic response. In this study creep test was carried out at temperature 5500C with constant stress 333.3 MPa, and creep-thermal cycling test was generated by constant stress during hold periods at maximum temperature 5500C and at minimum temperature 4200C on low alloy steel with Grade 360 BS3059. The samples were held at minimum temperature in two different media; in a furnace and in air respectively. Fractographic studies of fracture surface features, metallographic studies of microstructure, and studies of chemical composition are presented in the failure analysis as an aid in determining the failure mode of superheater tube. In the case study of mechanical properties and metallographic examination using optical microscope as well as SEM and EDX showed that a failure of superheater boiler tube, involved a combination of creep, thermal fatigue, stress corrosion cracking and local overheating of material with code SA213. Under conditions of experimental simulation, the fracture surface in which the crack morphologies were wedge and cavity intergranular crack type can be classified as ductile fracture. Time to rupture for the creep-thermal cycling tests was longer than that for the static creep tests on low alloy steel superheater tube, which is strongly affected by holding periods, number of cycles and environment. The texture of superheater tube component that have failed during service (case study), which showed creep and creep-thermal fatigue specimen tested was similar to major texture {110} and minor texture {200} and{211}.